Optimasi Tablet Levofloksasin yang Mengandung Bahan Pengikat PVP K-30 dan Disintegran Vivasol - Dina Ayu Fatmawati; Bambang Widjaja; Dwi Setyawan (Jurnal Sains Farmasi & Klinis, 2017)
The aim of this research was to get optimal formula of levofloxacin tablet prepared with variation of PVP K-30 as binder and vivasol as disintegrant. The making of levofloxacin tablets was done by wet granulation. Tablet was prepared with various levels of PVP K-30 and disintegrant vivasol, compressed using a hydraulic press with 12 mm punch diameter, for 3 seconds. Physical quality (hardness, friability, and disintegration time) and dissolution rate of tablet was evaluated. The optimization of the formula was done by factorial design of 22 factorial experiments with 2 factors (PVP K-30 and vivasol) and 2 levels (2% and 4%). Optimization results showed that elevated levels of PVP K-30 increased tablet hardness, reduced friability of tablet, decreased disintegrating time, and increased dissolution rate of levofloxacin tablets. Meanwhile, elevated levels of vivasol increased the hardness of tablets, decreased the disintegrating time of tablets, decreased the dissolution rate of levofloxacin tablets, but did not affect the friability of tablets. In conclusion, the optimal tablet that meet the specifications of physical quality (hardness, friability, and disintegrating time) and dissolution rate was made by 2.4 to 3.7% of PVP K-30 and 2.0 to 3.2% vivasol as shown in the feasible area of design space.